Analysis of approaches to modelling the fuzzy control systems with extension of their functional capabilities - Cherniy, S.P.; Susdorf, V.I.; Buzikaeva, A.V.; Khrulkov, V.N. (EAI Endorsed Transactions on Energy Web, 2020)
The research covers the issues of complexity in formalization of complex control objects using conventional methods and algorithms, considers different approaches to modeling of these objects, as well as reviews the features of different methods for synthesis of intelligent control systems using multi-cascade fuzzy control. It also represents a tracking drive model based on two-stage system. The structural solution for such an intelligent system includes four fuzzy controllers, three of which use Mamdani inference algorithms, and the fourth one represents an intelligent switching device with Sugeno inference algorithm. The article demonstrates the use of multi-cascade control technology for implementation of spacial membership functions.